When Traditional Meets Modern Pedagogies: A Case Study of Ma`had Aly Situbondo - Mohammad Firmansyah; Hilmi Ridho; Aizat Khairi; Sofiatus Sobriyah; Rahwan Rahwan (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
The purpose of this research is to examine the learning of Ma`had Aly Situbondo students in formulating contemporary fiqh law by combining text (yellow book) and context (social reality). In addition, it wants to know the urgency of the science of fiqh and ushul fiqh as a scientific concentration of Ma`had Aly Situbondo in producing Mahasantrinya to become a cadre of jurists (mujtahids). This research uses a case study approach that adopts mostly qualitative research techniques. The primary data was obtained from interviews with several lecturers and students of Ma`had Aly Situbondo and direct observation of the research location. The secondary data is taken from reputable books and journals that discuss Ma`had Aly Situbondo, starting from its history, and regulations, to its development. This study concluded that in formulating contemporary fiqh law, Ma`had Aly Situbondo students combine textual, contextual, and critical approaches while maintaining traditional learning patterns as pesantren in general. The results of Mahasantri fiqh products are published in the Tanwirul Afkar (TA) magazine which contains themes or issues of fiqh law that have not been thoroughly discussed or problems that are currently actual (viral) in society. The character building of the Ma`had Aly Situbondo Mahasantri into a cadre of jurists (mujtahids) is inseparable from the role of the science of fiqh and ushul fiqh. The implications of this research have an impact on the scientific characteristics of Ma`had Aly Situbondo which is considered capable of integrating between shahibul manqul (revelation) and shahibul ma``qul (reason).